RIMES: An Instrument to Compare National Criminal Justice Policies From the Social Exclusion Dimension - Díez Ripollés, José Luis (International e-journal of criminal sciences, 2019)
This paper presents a validated tool for comparing national crime control systems in accordance to the social exclusion they generate on those groups prone to enter into conflict with the criminal law. We first explained why we have chosen social exclusion as guiding principle for comparing national criminal policies, instead of other more usual criteria like punitiveness. Then we describe objectives, methodology, development and final configuration of the comparative instrument, called RIMES. The instrument comprises 39 indicators made up of current punitive rules and practices concerning nine relevant fields of penal intervention. It is able to measure in a comprehensive manner the social exclusion caused on suspects, defendants, offenders and ex-offenders by crime control systems of diverse Western industrialized countries, in such a way that it makes possible to proceed to comparisons among the different countries. The tool was submitted to a double process of validation by inter-judge agreement, where about 100 well-known international experts from 18 Western developed countries took part. Last goal is to make available a reliable instrument for interpreting current criminal justice policy and fostering grounded criminal policy decisions.